Magic Mountain A Study of Thomas Mann's Novel Der Zauberberg - Weigand, Hermann J. (Hermann John), 1892-1985 (University of North Carolina Press, 1965)
Praised highly by Mann himself, Weigand's book (originally published in 1933) is an essential piece of criticism on Mann's monumental novel. In his study of "The Magic Mountain" Weigand comments on the novel's genre and organization before dissecting the themes of disease and mysticism, Mann's use of irony, and other aspects of this masterpiece of German literature.